Zirconia crown restoration on endodontically treated first premolar: A case report - Pribadi, Nirawati; Sylvia; Tri Maulinda, Wulan; Ciciliya (Universitas Airlangga, 2022)
Background: Endodontic treatment failure is frequently caused by insufficient coronal sealing or crown restorations. In the longterm, this reduces the dental prognosis. A widely used restoration material that has outstanding mechanical properties is zirconia. Purpose:This report's aim is to describe the management of zirconia crown restorations on first premolars after endodontic treatment. Case: A 54-year-old male patient complained of a lump in the upper right gum area and had a restoration done, but it frequently came off. The patient needs immediate treatment with a longer-lasting restoration. Case Management: Endodontic treatment was completed in a single visit, and a zirconia crown was used as a permanent restoration Conclusion: Zirconia crown restorations on first premolars after endodontic treatment provide aesthetic and promising results.